Mediator Microbial Biosensor Analyzers for Rapid Determination of Surface Water Toxicity - Kharkova, Anna; Arlyapov, Vyacheslav; Medvedeva, Anastasia; Lepikash, Roman; Melnikov, Pavel; Reshetilov, Anatoly (Sensors (Basel, Switzerland), 2022)
Microbial mediator biosensors for surface water toxicity determination make it possible to carry out an early assessment of the environmental object’s quality without time-consuming standard procedures based on standard test-organisms, and provide broad opportunities for receptor element modifying depending on the required operational parameters analyzer. Four microorganisms with broad substrate specificity and nine electron acceptors were used to form a receptor system for toxicity assessment. Ferrocene was the most effective mediator according to its high rate constant of interaction with the microorganisms (0.33 ± 0.01 dm3/(g × s) for yeast Saccharomyces cerevisiae). Biosensors were tested on samples containing four heavy metal ions (Cu2+, Zn2+, Pb2+, Cd2+), two phenols (phenol and p-nitrophenol), and three natural water samples. The «ferrocene- Escherichia coli» and «ferrocene-Paracoccus yeei, E. coli association» systems showed good operational stability with a relative standard deviation of 6.9 and 7.3% (14 measurements) and a reproducibility of 7 and 5.2% using copper (II) ions as a reference toxicant. Biosensor analysis with these systems was shown to highly correlate with the results of the standard method using Chlorella algae as a test object. Developed biosensors allow for a valuation of the polluted natural water’s impact on the ecosystem via an assessment of the influence on bacteria and yeast in the receptor system. The systems could be used in toxicological monitoring of natural waters.